2023
DOI: 10.3390/plants12183291
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus Acquisition Efficiency and Transcriptomic Changes in Maize Plants Treated with Two Lignohumates

Veronica Santoro,
Maria Cristina Della Lucia,
Ornella Francioso
et al.

Abstract: Lignohumates are increasing in popularity in agriculture, but their chemistry and effects on plants vary based on the source and processing. The present study evaluated the ability of two humates (H1 and H2) to boost maize plant performance under different phosphorus (P) availability (25 and 250 μM) conditions in hydroponics, while understanding the underlying mechanisms. Humates differed in chemical composition, as revealed via elemental analysis, phenol and phytohormone content, and thermal and spectroscopic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 76 publications
0
0
0
Order By: Relevance
“…Likewise, Kong et al [61] showed that HA added to urea fertilizer reduced N loss and enhanced N use efficiency in maize and wheat. In addition, a significant increase in P use efficiency was found in maize, especially under low P conditions [62]. On the other hand, the highest doses of HS applied at both root and foliar (R4 and F4) caused a decrease in some NPK use efficiency parameters such as RE and AE, especially at R4.…”
Section: Discussionmentioning
confidence: 94%
“…Likewise, Kong et al [61] showed that HA added to urea fertilizer reduced N loss and enhanced N use efficiency in maize and wheat. In addition, a significant increase in P use efficiency was found in maize, especially under low P conditions [62]. On the other hand, the highest doses of HS applied at both root and foliar (R4 and F4) caused a decrease in some NPK use efficiency parameters such as RE and AE, especially at R4.…”
Section: Discussionmentioning
confidence: 94%